Oviposition Preference and Offspring Performance in Phytophagous Fruit Flies (Diptera: Tephritidae): The African Invader, Bactrocera invadens - Akol, A. M.; Masembe, C.; Isabirye, B.E.; Kukiriza, C. K.; Rwomushana, I. (International Research Journal of Horticulture, 2013)
Behavioral choices have been hypothesized to reflect fine-tuned evolutionary adaptation by the preference-performance hypothesis (PPH), which states that female insects will evolve to oviposit on hosts on which their offspring fare best. The extent to which this is true in the African invader, Bactrocera invadens (Diptera: Tephritidae) was assessed in this study. Five host-plant species: Terminalia catappa (Combretaceae), Persea americana (Lauraceae), Psidium guanjava (Myrtaceae), Mangifera indica (Anacardiaceae), and Citrus sinensis (Rutaceae), and 11 mango varieties: Tommy, Zillatte, Keitt, Kent, Kagogwa, Apple, Palvin, Dodo, Kate, Biire and Glen, were tested for their conformity to the PPH. The fruits were incubated, larvae reared, and the adults maintained on an artificial diet in the laboratory. There was significant variability in host species (P = 0.038) and variety (P = 0.015) preference in the orders: T.catappa > P.guanjava > M. indica > C. sinensis > P.americana; while Glen & Biire and Zillate & Tommy were the most and least preferred varieties, respectively. Offspring performance (development rate, survival, weights and sex ratio) differed significantly and followed a very similar trend only that for fruit species P.americana performed better than C. sinensis. The relationship between host preference and the offspring performance measures showed strong support for the PPH with overall coefficient of determination of 75.4% (P = 0.000) and 65% (P = 0.003) for host species and varieties, respectively. This study has generally increased the knowledge on the role of host species and varieties on the biology of the pest and re-affirmed the growing credence that host-specific variation in adult performance has an important role in shaping host preference of phytophagous insects, as proposed by PPH.
Keywords: Bactrocera invadens, Offspring Performance, Oviposition Preference, Tephritidae